CONTACT ANGLE ESTIMATION THROUGH GAUSSIAN SMOOTHING QUANTIFICATION - Louro, Antonio Henrique Figueira; Lima, Swami de Paula; Abijaude, Jauberth Weyll (Editora Impacto Científico, 2025)
This paper presents a new method for measuring the contact angle of sessile droplets. The method is based on Gaussian smoothing of a binary image of a droplet, followed by subtraction of its binary version. This result quantifies the smoothing produced at each pixel. Due to the circular symmetry of the 2D Gaussian, it is possible to establish a direct relationship between the smoothing produced at the pixel and the angular configuration of its surroundings. The method is quite accurate and, in the case of images with good contrast, the procedure can be fully automated, requiring only that the operator indicate the contact line between the droplet and the solid surface.DOI: https://doi.org/10.56238/edimpacto2025.034-008